Δ13C values of bacterial hopanoids and leaf waxes as tracers for methanotrophy in peatlands. (1st September 2019) - Inglis, Gordon N.; Naafs, B. David A.; Zheng, Yanhong; Schellekens, Judith; Pancost, Richard D.; ,
Abstract: Methane emissions from peatlands contribute significantly to atmospheric CH4 levels and play an essential role in the global carbon cycle. The stable carbon isotopic composition (δ 13 C) of bacterial and plant lipids has been used to study modern and past peatland biogeochemistry, especially methane cycling. However, the small number of recent peatlands that have been characterised and the lack of consistency between target compounds means that this approach lacks a rigorous framework. Here, we undertake a survey of bacterial and plant lipid δ 13 C values in peatlands from different geographic regions, spanning a wide range of temperature (−8 to 27 °C) and pH (∼3 to 8), to generate a reference dataset and probe drivers of isotopic variability. Within our dataset, the carbon fixation pathway predominantly determines leaf wax ( n -alkane) δ 13 C values. Bacterial-derived C31 hopane δ 13 C values track those of leaf waxes but are relatively enriched (0 to 10‰), indicating a heterotrophic ecology and preferential consumption of 13 C-enriched substrates (e.g. carbohydrates). In contrast, ≤C30 hopanoids can be strongly 13 C-depleted and indicate the incorporation of isotopically light methane into the bacterial community, especially at near neutral pH (∼5–6 pH). Previous analysis of Eocene sediments has suggested isotopic decoupling between C31 and ≤C30 hopanoid δ 13 C values. Our work suggests a globally widespread decoupling in recent peatlands; this persists despite the profound diversity of hopanoid producing bacteria and associated controls on their δ 13 C values and it has significant implications for future work. Re-analysis of published data from: (1) the (mid-to-early) Holocene and late Glacial, and (2) latest Paleocene and earliest Eocene in this revised context highlights that perturbations to the peatland methane cycle occurred during the past, and we envisage that this approach could provide unique (qualitative) insights into methane cycling dynamics throughout the geological record.